Regular Teacher Collaboration in the Learning Process at the School of Inclusion Organizers - yuana rizki fitri; Hermanto Hermanto (Department of Special Education, 2019)
This article discusses the importance of collaboration between regular teachers and special class teachers in the Learning Process of children with special needs in inclusive schools. During collaboration, regular teachers develop their competencies and learn from their peers how to apply the knowledge gained in practice. Collaborative teaching provides opportunities for pedagogy to share their knowledge, skills and experiences. While for students is an opportunity to get more diverse support and education. Collaborative systems can also facilitate the tasks of teachers in. The implementation of collaboration systems in inclusive schools on teacher learning processes is very important and has implemented a collaboration system in the Co-Teaching model with one teaching, one assist with the inclusive classroom system used is a pull out system.